Aspects of Integrated Water Resources Management in River Basins Influenced by Mining Activities in Lower Lusatia - Schoenheinz, Dagmar; Grünewald, Uwe; Koch, Hagen (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
In Lower Lusatia, eastern Germany, the changing impacts of lignite coal mining and potential climate change have put the naturally low water yield conditions under pressure. Water resources balances describe the hydrological situation in the region and the need for action due to changing boundary conditions. Extended transfer of flood water from neighbouring catchments is considered inevitable for sustainable regional development and the establishment of a quantitatively and qualitatively selfregulated water system. Using the river basin management system WBalMo®, potential water transfer scenarios to compensate for water deficits resulting from regional and global change are analysed.